2018
DOI: 10.1017/s1047951117002402
|View full text |Cite
|
Sign up to set email alerts
|

Utility of arterial stiffness assessment in children

Abstract: Atherosclerotic cardiovascular disease is a leading cause of death and disability worldwide, and the atherosclerotic process begins in childhood. Prevention or containment of risk factors that accelerate atherosclerosis can delay the development of atherosclerotic cardiovascular disease. Although current recommendations are to periodically screen for commonly prevailing risk factors for atherosclerosis in children, a single test that could quantify the cumulative effect of all risk factors on the vasculature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 123 publications
(237 reference statements)
1
35
1
5
Order By: Relevance
“…Patients with complex congenital heart disease are noted to be prone to ischemic cerebral injury, with progressive risk complicating the development of traditional cardiovascular risk factors with aging, resulting in ongoing risks to cognitive performance . The development of atherosclerotic disease is now recognized to progress from childhood, with ultrasound measures to assess vascular function identified as an important modality . Abnormal carotid artery resistance is associated with increased stroke risk; transcranial Doppler techniques have identified abnormal resistance in cerebral arteries in patients with diabetes, a group prone to adverse cerebral vascular events, as well as in adult patients with a background of aortic coarctation repair, similarly documented to be at risk of adverse cerebral events .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with complex congenital heart disease are noted to be prone to ischemic cerebral injury, with progressive risk complicating the development of traditional cardiovascular risk factors with aging, resulting in ongoing risks to cognitive performance . The development of atherosclerotic disease is now recognized to progress from childhood, with ultrasound measures to assess vascular function identified as an important modality . Abnormal carotid artery resistance is associated with increased stroke risk; transcranial Doppler techniques have identified abnormal resistance in cerebral arteries in patients with diabetes, a group prone to adverse cerebral vascular events, as well as in adult patients with a background of aortic coarctation repair, similarly documented to be at risk of adverse cerebral events .…”
Section: Discussionmentioning
confidence: 99%
“…For this measurement, pressure is applied to applanate (flatten) the artery using a special probe creating a signal that approximates arterial pressure. 10,24 For the PWV, waveforms of the right carotid artery and the right femoral artery were obtained. The waveforms of the carotid and femoral arteries were recorded sequentially gated by the R-wave on a simultaneously recorded electrocardiogram.…”
Section: Methodsmentioning
confidence: 99%
“…8 In addition, other factors such as hypertension and dyslipidemia may accelerate this process. 10 It has also been suggested that AS is influenced by gender and puberty, caused by differences in sex steroids. 11 Estrogens are assumed to decrease AS while androgens are proposed to promote it, causing higher AS in boys compared with girls.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations